1992
DOI: 10.1111/j.1432-1033.1992.tb17470.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of the Gly2 and Gly3 peptide oxygens of [Leu5]‐enkephalin in aqueous solution as revealed by the combined use of 17O‐NMR and Fourier‐transform infrared spectroscopy

Abstract: Solvent-induced and temperature-induced ' 0 chemical shifts of , LeuSI-enkephalin and solvent-induced spectral modifications of the amide-I' stretching vibrations of [1-13C-Gly2, Leu51-enkephalin and [1-13C-Gly2, Leu51-enkephalin are reported and correlated with the spectroscopic characteristics of model amides. It is demonstrated that both Gly2 and Gly3 peptide oxygens are motionally equivalent and form solvation species which are essentially monohydrated in aqueous solution, contrary to several simple amides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…Meanwhile, the loss of regular secondary structures could be monitored by the intensity changes of the amide I band. This correlation has been well-studied in helical peptides [22][23][24][25]27], but is addressed in limited numbers of proteins composing various secondary structures. To verify the hypothesis concerning band frequency and hydration states above, we studied the behavior of the thermal transition of RNase A as a model system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the loss of regular secondary structures could be monitored by the intensity changes of the amide I band. This correlation has been well-studied in helical peptides [22][23][24][25]27], but is addressed in limited numbers of proteins composing various secondary structures. To verify the hypothesis concerning band frequency and hydration states above, we studied the behavior of the thermal transition of RNase A as a model system.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, it has long been recognized that the IR amide bands are affected by the microenvironments of the secondary structures [21]. Since the carbonyl oxygen groups of polypeptides can form hydrogen bonds with water during protein hydration, the peak-shift of the amide I band provides a means to monitor the hydration states of secondary structures and this has recently been applied to reflect the extent of hydration in the thermal transition of -helical peptides [22][23][24][25][26][27]. These studies revealed a good correlation of the movement of the IR band from the -helix and the solvation of peptide backbone at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…c The trans isomer which largely exists in a b-turn intramolecular hydrogen bonded form [311]. d The peptide oxygens are supposed to form largely monohydrates [312,313]. Care has to be taken, however, in using these correlations, because they are restricted to special applications.…”
Section: Empirical Correlations [256]mentioning
confidence: 99%
“…167). For Gerothanassis et al [313,775] investigated in detail Leuenkephalin (Tyr-Gly-Gly-Phe-Leu) which is a brain neurotransmitter peptide that has been extensively investigated during the past 30 years with a variety of spectroscopic methods. Both ( 17 O-Gly2, Leu5)-enkephalin and ( 17 O-Gly3, Leu5)-enkephalin have similar 17 O chemical shifts in CH 3 CNADMSO (4:1; vol.)…”
Section: Peptidesmentioning
confidence: 99%